Flow characteristics of the wind-driven current with submerged and emergent flexible vegetations in shallow lakes - 王超 范秀磊 王沛芳 侯俊 钱进 (水动力学研究与进展：英文版, 2016)
A pneumatic annular flume is designed to simulate the current induced by the wind acting on the water surface in shallow lakes and the experiments are conducted to investigate the influence of submerged and emergent flexible vegetations of different densities on the flow characteristics(e.g., the flow velocity, the turbulence intensity, the vegetal drag coefficient DC and the equivalent roughness coefficient bn) at different wind speeds. Vallisneria natans(V. natans) and Acorus calamus(A. calamus) widely distributed in Taihu Lake are selected in this study. It is indicated that the vertical distribution profiles are in logarithmiccurves. The stream-wise velocity rapidly decreases with the increasing vegetation density. The flow at the lower layer of the vegetation sees compensation current characteristics when the vegetation density is the largest. The turbulence intensity in the flume without vegetation is the highest at the free surface and it is near the canopy top for the flume with V. natans. The turbulence intensity near the bottom in the flume with vegetation is smaller than that in the flume without vegetation. A. calamus exerts much larger resistance to the flow than V. natans. The variations of DC and bn caused by the vegetation density and the wind speed are also discussed.